2019
DOI: 10.3390/su11185010
|View full text |Cite
|
Sign up to set email alerts
|

Is It Time to Shift Our Environmental Thinking? A Perspective on Barriers and Opportunities to Change

Abstract: In 2015, the United Nations General Assembly unanimously adopted the 2030 Agenda for Sustainable Development and Sustainable Development Goals. In 2019, the release of the global assessment report of the United Nations’ Intergovernmental Platform on Biodiversity and Ecosystem Services unfortunately demonstrated that our planet may be in more trouble than expected. The main drivers have been identified for many years and relate to human activities such as over-exploitation of natural resources leading to land d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This topic also includes how social media can help achieve sustainability transformation. Daigle and Vasseur emphasized the need for transformational change as the Earth is reaching the limit of its resources, and they suggested that the solution can come from education and social media [78]. Intensifying the government's narratives in social arenas through the use of newspapers and social media platforms can help to make environmental issues more politically and socially relevant [79,80].…”
Section: Review Of Topicsmentioning
confidence: 99%
“…This topic also includes how social media can help achieve sustainability transformation. Daigle and Vasseur emphasized the need for transformational change as the Earth is reaching the limit of its resources, and they suggested that the solution can come from education and social media [78]. Intensifying the government's narratives in social arenas through the use of newspapers and social media platforms can help to make environmental issues more politically and socially relevant [79,80].…”
Section: Review Of Topicsmentioning
confidence: 99%
“…(Rees 1992;Wackernagel et al 1999). This global issue developed in the 1990s (Rees 1992;Wackernagel et al 1999) and has attracted the attention of many researchers in various fields, policymakers and so far (Including studies by Ogata 2002;Curutchet et al 2012;Hynes and Wang 2012;Ciarreta et al 2014;Enfedaque and Martínez 2014;Robert and Castañeda 2014;Kattumuri 2018;Sarkodie 2018;Daigle and Vasseur 2019;Kotcher et al 2019;Wang et al 2019). Over the past ten years, the EF in the European Union has increased further, reaching 4.6 gha/person in 2016.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature of the subject refers to education as a critical factor determining the achievement of sustainable development goals (Hansmann and Binder, 2020;Wiek et al, 2011). Education ought to encompass all education levels (Daigle and Vasseur, 2019;Kapitulcinova et al, 2018), starting with pre-school and up to university studies.…”
Section: Introductionmentioning
confidence: 99%